Paths Out of Poverty : The Role of Private Enterprise in Developing Countries - International Finance Corporation (Washington, DC, 2013)
Following on the work of previous, recent publications - Voices of the Poor, and the World Development Report 2000/01 - this report provides missing mechanisms by which people, and countries emerge from poverty, arguing that income, results to the extent that democracy, opportunity, and other positive factors encourage the productive units in the economy, i.e., private enterprises. It focuses on the sources of economic, and social mobility that lift people out of poverty: competition, deregulation, liberalization, and open trade, forces that weaken the nexus of privilege, that perpetuate poverty in many countries. Private enterprise as an engine of upward mobility, requires the proper support from the state, though extreme views - both the Marxist view of capitalist firms, and the extreme neoclassical model of a level playing field that makes lobbying ineffective - are clearly off base. Rather, the report reviews doing business and reducing poverty, based on the rule of law, and the establishment of sound economic policies. As well, innovations, supported by an adequate infrastructure, and the right privatization, and deregulation process, are factors conducive to sustainable economic expansion.